Conservative Approach for Restoring Posterior Missing Tooth with Fiber Reinforcement Materials: Four Clinical Reports - Karaarslan, Emine Sirin; Ertas, Ertan; Ozsevik, Semih; Usumez, Aslihan (European Journal of Dentistry, 2011)
Adhesively luted, fiber-reinforced, composite-inlay, retained fixed-partial dentures can be a clinical alternative for the replacement of missing posterior teeth in selective situations. This type of restoration allows for satisfactory esthetics and reduced tooth preparation compared to a conventional, fixed-partial denture. This clinical report describes the use of a fiber-reinforced, compositeinlay, retained fixed-partial denture as a conservative alternative for the replacement of missing posterior teeth. (Eur J Dent 2011;5:465-471)
Keywords: Missing posterior teeth; Inlay; Fixed-partial denture